Critical analysis of modern technologies and formulations of non-autoclaved aerated concrete for production conditions in the Republic of Uzbekistan (Международный научный журнал «Инженер», 2026)
Foam concrete is a modern and efficient thermal insulation material, representing a system of interconnected air cells within a cement matrix. Considering the promising potential for improving technologies and compositions of foam concrete, further development of formulation and technological approaches is justified. A critical analysis concludes that the introduction of fiber and a modifying component, combined with chemical additives acting as hardening accelerators, positively affects the operational properties of foam concrete and the rheological characteristics of foam-cement mixtures.